"Corporate governance" and performance in nonprofit organizations. (May 2022) - Blevins, Dane P; Ragozzino, Roberto; Eckardt, Rory
Corporate governance has received substantial scholarly attention for decades, although the focus of this research has by and large been on publicly traded for-profit organizations. However, agency problems are increasingly recognized in nonprofits. As such, we examine the application of corporate governance logic in the context of nonprofits. Our study relies on nearly a decade of data spanning 6853 US-based charities and comprising nearly US$346 billion in total revenue. Our results show that common corporate governance practices—such as independent boards, chief executive officer oversight, and transparency—enhance the degree to which donor contributions are allocated toward a charity's mission. Overall, we assess the broader applicability and benefits of corporate governance and build on literature highlighting links between for-profit and nonprofit organizations. In doing so, we demonstrate the usefulness of governance in this economically and socially consequential context.